2020
DOI: 10.1038/s41467-020-16568-z
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of essential amino acids dictates the systemic metabolic response to dietary protein dilution

Abstract: Dietary protein dilution (DPD) promotes metabolic-remodelling and-health but the precise nutritional components driving this response remain elusive. Here, by mimicking amino acid (AA) supply from a casein-based diet, we demonstrate that restriction of dietary essential AA (EAA), but not non-EAA, drives the systemic metabolic response to total AA deprivation; independent from dietary carbohydrate supply. Furthermore, systemic deprivation of threonine and tryptophan, independent of total AA supply, are both ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
103
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 88 publications
(181 reference statements)
11
103
0
1
Order By: Relevance
“…Here, we show that, particularly during meal feeding tests, the blood plasma levels of essential amino acids isoleucine, leucine, valine (i.e., branched chain AA), lysine, phenylalanine, and threonine, as well as the non-essential AA tyrosine, were lower in young men undergoing DPR compared with their habitual diet. A similar signature was found in our former studies of mice [9,17], demonstrating mammalian conservation of these responses. Additionally, this AA signature is reminiscent of several studies that have shown higher blood levels of these amino acids as predictive of current or future type 2 diabetes risk in humans [19][20][21].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Here, we show that, particularly during meal feeding tests, the blood plasma levels of essential amino acids isoleucine, leucine, valine (i.e., branched chain AA), lysine, phenylalanine, and threonine, as well as the non-essential AA tyrosine, were lower in young men undergoing DPR compared with their habitual diet. A similar signature was found in our former studies of mice [9,17], demonstrating mammalian conservation of these responses. Additionally, this AA signature is reminiscent of several studies that have shown higher blood levels of these amino acids as predictive of current or future type 2 diabetes risk in humans [19][20][21].…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, THR restriction without total AA restriction mimics the effects of DPR in mice, without the negative side-effects of reduced skeletal muscle mass [17]. In addition, we previously demonstrated that dietary THR restriction improves metabolic health in a pre-clinical mouse model of obesity driven type 2 diabetes [17]. Thus, future studies should closely examine the effects dietary threonine restriction in humans.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations